Computers and Tuvan language: an overview of research at Tuvan State University - Dalaa, Sergey M. (The New Research of Tuva, 2016)
Since their very beginnings, both philology and information technologies have faced the challenge of processing textual information. With the arrival of the Internet, this task has become more topical than ever before. In the Republic of Tuva, it is being dealt with by the Research and Education Center for Turkic Studies at the Tuvan State University in collaboration with the university’s Department of Information Technologies. This article is an overview of their joint projects. Computer processing of texts in Tuvan used to be a difficult task since the Tuvan alphabet is Cyrillic-based, but makes use of three letters absent in Russian - ң, ө and ү which did not have special codes assigned before the arrival of UNICODE. When the spread of UNICODE began in 1990s, Tuvan texts finally could be coded in their entirety. The article provides short summaries and abstracts of databases and software created by Tuva’s researchers in collaborative projects and registered at the Federal Service for Intellectual Property (Rospatent) in 2013-2015. All patent rights belong to Tuvan State University. The list includes such pieces of software as “Chastotnyi slovar po khudozhestvennym proizvedeniiam na tuvinskom iazyke” (Frequency dictionary of literary texts in Tuvan language), “Poisk slov v tekste na tuvinskom iazyke” (Word search in Tuvan texts), “Tyva dyl. Sөzүglel. Praktiktig stilistika 10-11 klasstarga өөredilge nomu” (Practical stylistics for 10th and 11th grades), “Leksika landshafta Tuvy” (The vocabulary of Tuvan landscape), CMS “Pisateli Tuvy” (The writers of Tuva), databases “Slovar’ dialektnykh slov altaiskogo dialekta Tuvinskogo iazyka” (A vocabulary of the Altai dialect of Tuvan language), Morfemno-orfograficheskii slovar’ Tuvinskogo iazyka” (Morphemic and orthographic dictionary of Tuvan language), and “Analiticheskie skrepy Tuvinskogo iazyka” (Analytical foundations of Tuvan language) Given the rise of mobile devices and the variety of platforms for mobile software (Android, iOS, Windows Phone, etc.), development of mobile apps of various types is a highly topical challenge at the moment.